Relationship between the processes of reading comprehension and metacognitive reading skills in Peruvian students of 5th and 6th grade of elementary school - Guere Paredes , Omar Pedro (2024)
The objective of this research is to determine the relationship between the processes that make up reading comprehension (perceptive, lexical, syntactic and semantic) and the metacognitive reading skills (planning, supervision and evaluation) in students of cycle V (5th and 6th grade of elementary school) from a private school, located in the district of Santiago de Surco, Lima (Peru). The instruments used were the Battery of Evaluation of the Reading Processes - Revised (PROLEC-R) and adapted for students of Metropolitan Lima, and the Scale of Reading Consciousness (ESCOLA). The sample consisted of 80 students (50 of the 5th grade and 30 of the 6th grade), being a non-probabilistic by convenience, sampling. The results show that there is a correlation between the variables (at a global level and for each process); however, this relationship occurs at various levels of significance. The syntactic process was the one that showed the best results, reaching very significant levels (p<.01) in almost all the relationships evaluated.